Informacja publiczna a tajemnica przedsiębiorcy - Cybulska, Renata (PRAWO i WIĘŹ, 2025)
Access to public information is a right guaranteed not only by acts, but above all by the provisions of the Polish Constitution. However, it is not an unconditional right, as it is subject to certain restrictions, specified, inter alia, in Article 47 of the Polish Constitution and Article 5 of the Act on Access to Public Information. One such restriction on obtaining public information is trade secret. Due to the growing number of requests for access to information containing this secret, this study presents the most important issues related to this topic.